Diseño de un sistema de gestión de calidad en el área de inmunología del laboratorio de docencia del Centro de Diagnóstico Médico de la Universidad Nacional de Loja según la Norma ISO-9001- - Ludeña Ordoñez, Miller Gabriela (2024)
The teaching laboratories of the Clinical Laboratory career can be defined as an area where theoretical and practical knowledge is put into practice, allowing students to develop the skills, knowledge and attitudes necessary for their future professional development and for significant learning, in which they must comply with a quality management system, which allows the application of the methods and standards indicated in the ISO Standards. The result is high precision, reliability and punctuality in the student's theoretical and practical learning. Context under which the present research aims to design a quality management system in the immunology area of teaching. Minimizing errors and managing to offer quality learning results that meet the needs and laboratory standards of the Medical Diagnostic Center of the National University of Loja according to the ISO-9001-2015 Standard. To comply with the established objectives, a study was carried out with a qualitative, descriptive and exploratory approach; where in the first stage an initial diagnosis was carried out with an internal audit, in which it was identified that the area of immunology does not currently have any requirements of the ISO 9001 2015 Standard, subsequently the update and design of the documented information related to the quality management system, managing to ensure quality in the educational service, expectations of students and teachers